2016
DOI: 10.1042/cs20160116
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic- and antidepressant-like effects of angiotensin-(1–7) in hypertensive transgenic (mRen2)27 rats

Abstract: Angiotensin-(1-7) [Ang-(1-7)], a counter-regulatory peptide of the renin-angiotensin system (RAS) exerts its effects through the G-protein-coupled receptor Mas, which is expressed in different tissues, including the brain. Ang-(1-7) has a broad range of effects beyond the well-described cardiovascular and renal actions, including the modulation of emotional and behavioural responses. In the present study we tested the hypothesis that Ang-(1-7) could attenuate the anxiety- and depression-like behaviours observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Accordingly, years later Bild and Ciobica (43) showed an anxiolytic-like effect after chronic ICV infusions of ANG-(1-7), accompanied by a reduction in oxidative stress in the amygdala. More recently, using two different transgenic rat lines, we showed that ANG-(1-7) ICV infusions could attenuate anxiety-like behavior (11,272). In addition, we showed that ANG-(1-7) was also effective in attenuating a depression-like phenotype (11).…”
Section: Other Angiotensin-(1-7) Effects In the Brainmentioning
confidence: 86%
See 2 more Smart Citations
“…Accordingly, years later Bild and Ciobica (43) showed an anxiolytic-like effect after chronic ICV infusions of ANG-(1-7), accompanied by a reduction in oxidative stress in the amygdala. More recently, using two different transgenic rat lines, we showed that ANG-(1-7) ICV infusions could attenuate anxiety-like behavior (11,272). In addition, we showed that ANG-(1-7) was also effective in attenuating a depression-like phenotype (11).…”
Section: Other Angiotensin-(1-7) Effects In the Brainmentioning
confidence: 86%
“…More recently, using two different transgenic rat lines, we showed that ANG-(1-7) ICV infusions could attenuate anxiety-like behavior (11,272). In addition, we showed that ANG-(1-7) was also effective in attenuating a depression-like phenotype (11). Interestingly, hypertensive patients who suffer from depression exhibit mood improvements after treatment with the ACE inhibitor captopril, which increases levels of ANG-(1-7) (50).…”
Section: Other Angiotensin-(1-7) Effects In the Brainmentioning
confidence: 90%
See 1 more Smart Citation
“…Administering Ang-(1-7) was associated with decreased oxidative stress markers in the amygdala [ 180 ]. The same Mas antagonism also prevented the anxiolytic/antidepressant effect of enalapril in transgenic hypertensive rats [ 181 , 182 ].…”
Section: Major Depressive Disorder (Mdd) and Neuroinflammation: Pre-cmentioning
confidence: 99%
“…Central Ang(1–7) treatment of hypertensive (mRen2)27 transgenic rats attenuates the anxiety and depression‐like behaviour in these animals (Almeida‐Santos et al, ; Wang et al, ). In a chronic constriction injury rat model, intrathecal administration of Ang(1–7) relieves, whereas A‐779 aggravates injury‐induced neuropathic pain (Zhao et al, ).…”
Section: Experimental Model Studiesmentioning
confidence: 99%